2014
DOI: 10.1111/risa.12247
|View full text |Cite
|
Sign up to set email alerts
|

Concerns, Challenges, and Directions of Development for the Issue of Representing Uncertainty in Risk Assessment

Abstract: In the analysis of the risk associated to rare events that may lead to catastrophic consequences with large uncertainty, it is questionable that the knowledge and information available for the analysis can be reflected properly by probabilities. Approaches other than purely probabilistic have been suggested, for example using interval probabilities, possibilistic measures, or qualitative methods. In the present paper, we look into the problem and identify a number of issues which are foundational for its treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(100 citation statements)
references
References 74 publications
0
99
0
1
Order By: Relevance
“…For this reason many researchers and risk analysts prefer to use other approaches for representing the epistemic uncertainties, including those based on interval probability, possibility theory and evidence theory, as well as qualitative methods reflecting the strength of the background knowledge K [10]. For the sake of simplicity these alternative approaches are referred to as non-probabilistic methods.…”
Section: The Concepts Of Probability and Riskmentioning
confidence: 99%
“…For this reason many researchers and risk analysts prefer to use other approaches for representing the epistemic uncertainties, including those based on interval probability, possibility theory and evidence theory, as well as qualitative methods reflecting the strength of the background knowledge K [10]. For the sake of simplicity these alternative approaches are referred to as non-probabilistic methods.…”
Section: The Concepts Of Probability and Riskmentioning
confidence: 99%
“…An important aspect of modeling uncertainties lies in the appropriate selection of the time window, which is used for the inclusion of data [33]. The traditional empirical approach can lead to either a too conservative or non-conservative estimates of the magnitude of uncertainties based on the arbitrary choice of the length of time window [17].…”
Section: Introductionmentioning
confidence: 99%
“…While sensitivity evaluation experiments on the measurement of subjective probability seem to suggest that numeric measures outperform other scales (Haase et al 2013), in some situations single-valued probability is not considered adequate to represent uncertainty, and non-probabilistic measures interpreted as lower and upper probabilities are seen as more appropriate (Flage et al 2014). It has also been observed that certain uncertainties in scientific advice to policy-makers are not caused by probabilistic predictions, but could originate from a fundamental lack of understanding of new phenomena at or beyond the frontiers of present knowledge (May 2001).…”
Section: Managing Uncertainties In Risk Managementmentioning
confidence: 99%
“…The authors of an international perspective paper (Flage et al 2014) report that measurement of uncertainty within risk assessment can be varied: subjective probability, non-probabilistic representations with interpretations as lower and upper probabilities, non-probabilistic representations with other representations such as degree of belief, degree of possibility, hybrid combinations of probabilistic and non-probabilistic representations and semi-quantitative approaches. They also suggest that where risk analysis of large uncertainties is conducted, probabilities may not reflect the knowledge or information available and recommend the need for an extended framework for risk assessment which reflects the separation that exists between the analyst and decision-maker.…”
Section: Managing Uncertainties In Risk Managementmentioning
confidence: 99%